3-Methyl-4-Nitrobenzoate Derivates as Antifungal Drug Candidates: Biological and In Silico Evaluation - Alana R. Ferreira; Yunierkis P. Castillo; Ana C. M. Andrade; Diego F. Nóbrega; João Paulo G. de Oliveira; Tamires C. Lima; Ricardo D. de Castro; Damião P. de Sousa (Journal of Chemistry)
The Candida genus includes many opportunistic pathogens of great clinical importance, being commonly involved in several superficial and systemic human fungal infections. In this study, eleven 3-methyl-4-nitrobenzoate derivates were prepared and evaluated against four Candida strains (Candida albicans ATCC-90028, C. glabrata 90,030, C. krusei 34,125, and C. guilliermondii 207). The relationship between the chemical structure of the prepared compounds and their antifungal activity was also investigated. The chemical structure of the obtained products was confirmed using Infrared, 1H and APT-13C nuclear magnetic resonance spectroscopy and high-resolution mass spectrometry. The antifungal assay results showed that the screened compounds exhibited different levels of activity depending on the structural variation and tested strain. Among the 11 nitrobenzoate analogs, the compounds methyl 3-methyl-4-nitrobenzoate (1) and pentyl 3-methyl-4-nitrobenzoate (6) presented great antifungal activity against C. guilliermondii 207, with MIC values of 39 and 31 µM, respectively. Modeling studies of 6, the most bioactive compound against C. guilliermondii, demonstrated that it interacted with TPMK protein, which has been proposed as a molecular target in studies of potential antifungal agents. Finally, the preliminary SAR study of this series furnished information on possibly structural features that may affect the antifungal activity, like the importance of alkyl side chains for bioactivity.